The Dilemma of Nursing Home Closures: A Case Study of Rural Maine Nursing Homes - McSweeney-Feld, Mary; Braunstein, Nadine (Maine Policy Review, 2020)
Nursing home closures in the United States have accelerated in the past five years. Reasons for these closures include inadequate Medicaid reimbursement, increased emphasis on short-term rehabilitative stays for Medicare residents, geographic location of nursing homes, presence of hospital swing bed programs, and changes in Center for Medicare and Medicaid Services regulatory requirements for nursing homes. Increased minimum wage rates and limited on-the-job worker training have also led to staffing shortages, forcing bed reductions in nursing homes. This paper examines the premise that low Medicaid reimbursement is the primary reason for the closures of Maine nursing homes. The article evaluates state cost assumptions that determine Medicaid payments for skilled nursing care, programs for long-term care workforce development, and growth in service alternatives from hospital swing bed programs to home- and community-based services.